A Recursive Algorithm for Set-Valued Observers with Dynamic Uncertainties - Morel, Jorge O. (2000)
In this work we present a new algorithm for set-valued state propagation in observers with dynamic uncertainties. In comparison with recently results published in the specialized literature, the novel approach presents the same numerical features and equal bound tightness for state uncertainties, but additionally has the advantage of distributing the  computational burden uniformly in time. This makes the approach attractive for on-line applications. Convergence results for the centroids of the state polytopes are given in the presence of bounded state and output perturbations.